Organic solvents for enhanced efficacy of carbendazim against Sclerotinia rot of sunflower - J.P. GUPTA, M. ARUNA KISHORE and (Indian Phytopathology, 2002)
Pot experiments were conducted to investigate the quantitative distribution of carbendazim in sunflower and the subsequent control of Sclerotinia rot caused by S. sclerotiorum following seed treatment by the organic solvent infusion technique (OSIT). Seeds of sunflower variety Morden were treated with carbendazim at 0.05 or 0.1% by conventional seed dressing or OSIT. Solutions of carbendazim were prepared in acetone or carbon tetrachloride (CTC) and the seeds were immersed for 4 hours before drying and sowing in pots in the greenhouse. Translocation of carbendazim in sunflower was significantly higher when seeds were treated with 0.05% carbendazim dissolved in acetone or CTC than dry seed treatment. Sclerotinia rot was effectively controlled (88.9and 83.3%, respectively) by these 2 treatments compared with only 66.7% disease control following dry seed treatment at 0.1%. Persistence of fungicide was highest (up to 45 days) when acetone was used as the solvent. It is concluded that acetone and CTC allow greater translocation of carbendazim within the plant and, therefore, efficient control of seed and soilborne pathogens can be achieved using minimal amounts of fungicide.